Um olhar sobre a sinalização em Bibliotecas Universitárias: à luz do wayfinding - Picado, Karin Herculano (2019)
This dissertation focuses on the construction of strategies for the creation and development of a academic library space orientation system, based on premises identified by recognized authors in the area of Information Design knowledge: Signage, Semiotics, Sensemaking and Wayfinding. The theme addressed in this research refers to issues related to the aesthetic and functional characteristics of spatial orientation in public spaces and the synergies between users and space. This work establishes as a proposal for the general objective to analyze the graphic material of the signaling system existing at the Central Library of the Federal University of Paraíba - UFPB a and at the Joacil de Britto Pereira Library of the Faculties Nova Esperança - FACENE / FAMENE in João Pessoa under the light of Wayfinding, in its technical, aesthetic and functional aspects, based on the Peircean semiotic school. For the development of this study, it was necessary to define a methodological strategy, where we used the research: applied, qualitative, exploratory, descriptive and a purposive wayfinding study, performed on the existing situation. In fulfillment of the objectives, we conducted the investigation, starting with a signaling inventory of the libraries selected for this sample. During the on-site research work, we developed the inventory form and sought to find out which flows were flagged as main, whether or not the signage resources used met users' needs and whether parts of the signage system would be arranged at their best. considering the main flows. With the resulting inventory, which corresponded to data collection, we performed the interpretation of these data, under the light of Peircean semiotics. After the analysis, with the results obtained and from the use of the 3-Step Unfolding Method - MD3E, together with the sensemaking perspective, we present a signaling project applicable to these environments based on the various concepts established for a Wayfinding Information System. (SIW). After expert readings, in-depth analysis of signage and signage projects designed for academic libraries, we believe it is possible to create wayfinding systems integrated with the architectural structure of any space, with a multidisciplinary look at the information environment. We note that these projects should always consider the way users attend and interact with these spaces (or not). We understand that there are important and mandatory principles in any wayfinding project, but it is good to note that each academic library has its own identity and that there is no project "ready" to be adopted without any adaptation. There was no pretense to work modifications in the structures of the libraries. The proposals presented here were made with the aim of creating a sense of unity in the spaces and facilitating the spatial orientation of anyone who enters a academic library and who can also find their way out without any effort.